Assessment of the Efficacy of Reflective Activities in Obstetrics and Gynecology Residents for Improving Certain Recognized Abilities - Naveed Fazal, Samreen Kishwar Abbasi, Sidra Masood, Tahira Fatima, Sadam Hussain, Rukhsana Shaheen Afzal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the efficacy of reflective activities in obstetrics and gynecology residents for improving certain recognized abilities. Methods: Continuously communicate permission, twenty-five patients from across all five years of the residency program have been included in the research. Surgical skills, professionalism, communication skills, and especially analytical thinking abilities were recognized as competencies. The introspective activities were evaluated using a foundation for the rest designed for this purpose. Results: The findings revealed that the resident’s capacity to participate in intentional reflecting activities was originally weak, but improved with practice and yielded promising results. In comparison to others made up to the mark, reflective exercises were very beneficial in improving training and expertise. Conclusion: Regularly engaging postgraduate trainees in intentional reflecting activities have yielded good outcomes in terms of growth in surgical, communicative, and quality assessment abilities, as well as a role in enhancing professionalism amongst residents. Prospective multicenter research, on the other hand, can provide more information about the efficacy of such a therapy. Keywords: Reflective Activities, Obstetrics and Gynecology, Residents.